Analgesic and Antipyretic Effects of Jamblang (Syzygium cumini (l). Skeel) Leaves Ethanol Extract - Mus, Suwahyuni; Rahimah, Sitti; Maryam, Fadhilla (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2022)
Analgesic-antipyretic is a compound used to reduce pain and fever. This study aims to determine whether the ethanol extract of Syzygiumium cumini leaves has analgesic and antipyretic activity in mice (Mus musculus) induced by acetic acid and peptone. The method used was the Writhing method with acetic acid induction fanalgesiasic and the rectal temperature measurement method for antipyretic testing. This research was started by extracting Syzygium cumini (L.) Skeels leaves with 70% ethanol solvent by maceration. Syzygium cumini (L.) Skeels leaves extract was then tested in 5 groups the s, positive control growth as up given paracetamol for antipyretic testing and mefenamic acid for analgesic testing, negative control group ( Na.CMC suspension), a dose of 6 mg/Kg, 9 mg/Kg and 12 mg/Kg of body weight. The results indicate that the ethanol extract Syzygiumium cumini leaves has analgesic and antipyretic activity at all treatment doses and the most effectivect is at a dose of 6 kg BW KEYWORD : Syzygium cumini (L) Skeels, Mice, Analgesic, Antipyretic